Toner

By using polyester resin core particles and amino resin shells in toner particles and adding polyvalent metals to the interface, the problems of toner fusion and shell peeling at high temperatures are solved, and high development durability and low temperature fixability are achieved.

CN114442446BActive Publication Date: 2025-04-18CANON KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111304447.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-06
Filing Date
2021-11-05
Publication Date
2025-04-18
Estimated Expiration
2041-11-05

AI Technical Summary

Technical Problem

The existing toner is prone to fused when stored at high temperatures, and the shell peeling of the core-shell toner during repeated printing results in developing defects, making it difficult to take into account both low-temperature fixability and development durability.

Method used

Toner particles containing polyester resin core particles and amino resin shells were used, and polyvalent metal was added at the core particle/shell interface, and the surface storage elastic modulus of the toner was optimized by energy dispersed X-ray analysis and nanoindentation measurement.

Benefits of technology

It effectively suppresses shell peeling, maintains low-temperature fixability, and improves development durability and reduces the occurrence of image defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005121131380000251
    Figure GDA0005121131380000251
  • Figure GDA0005121131380000331
    Figure GDA0005121131380000331
  • Figure GDA0005121131380000341
    Figure GDA0005121131380000341
Patent Text Reader

Abstract

The present invention relates to a toner. A toner includes toner particles, the toner particles including: a core particle containing a resin component, a shell covering the surface of the core particle, and a polyvalent metal. The resin component contains a polyester resin, and the shell contains an amino resin; in an electron image of a cross section of the toner taken using a transmission electron microscope, the content P(M) of the polyvalent metal obtained at and near the core / shell interface by energy dispersive X-ray analysis is 0.0010 to 2.00 atomic %; and according to nanoindentation measurement of the toner, the surface storage elastic modulus of the toner at 25°C under a load of 30 μN is 6.50 GPa to 12.00 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a toner for forming a toner image by developing an electrostatic latent image formed by a method such as an electrophotographic method, an electrostatic recording method, and a toner jet system recording method. Background Art

[0002] In recent years, methods such as electrophotography for visualizing image information by electrostatic latent images have been used in various fields, and copy machines and printers are required to be smaller, more energy-efficient, and have a longer life, as well as have higher image quality and higher speed.

[0003] Among these considerations, it is strongly desired to reduce the running cost of copiers and printers. As a result, excellent energy saving is required, as well as long life that can be printed for a long time by a single box. From the viewpoint of energy saving, a binder resin with a low melting point or glass transition temperature, and / or a release agent with a low melting point are usually used to prepare a toner showing excellent low temperature fixability, which in turn can reduce the power used during heat fixing. When such toners are stored at high temperatures, the problem of toner-to-toner fusion occurs easily.

[0004] In response to this problem, for example, Japanese Patent Application Laid-Open No. 2015-045844 discloses a core-shell toner using a thermosetting resin and a thermoplastic resin in a shell layer.

[0005] However, toner / toner contact and toner / member contact accompany all operations in a series of operations related to an image forming process for visualizing an electrostatic latent image using toner, and thus toner is repeatedly loaded to such an extent that such contact occurs. As a result, the toner subjected to such heating and stress presents problems of deformation and toner cracking and crushing.

[0006] In response to this problem, for example, Japanese Patent Application Laid-Open No. 2014-164274 proposes a toner in which the surface hardness and the displacement amount measured using a nanoindentation method fall within specific ranges. Summary of the invention

[0007] However, low temperature fixability and development durability are contradictory properties and it is found difficult to reconcile the requirements of modern design concepts. Regarding long-life development systems, it is found that when repeated printing is continuously performed using the above toners, the shell in the core-shell toner eventually peels off from the core particle.

[0008] When the shell is peeled off from the core particle, image defects are eventually generated due to disturbance of charging performance and because the peeled shell and exposed core particles contaminate and fuse to members involved in image formation, that is, developing members and charging members. Thus, there is still room for improvement in durability.

[0009] The present disclosure provides a toner that exhibits excellent long-term developability by suppressing shell peeling while exhibiting maintenance and improvement of low-temperature fixability.

[0010] The present disclosure relates to a toner, comprising toner particles, the toner particles comprising:

[0011] a core particle comprising a resin component,

[0012] a shell covering the surface of the core particle, and

[0013] Polyvalent metals, among which

[0014] The resin component comprises a polyester resin;

[0015] The shell comprises an amino resin;

[0016] In an electron image of a cross section of a toner particle taken using a transmission electron microscope,

[0017] The content P(M) of the polyvalent metal is 0.0010 to 2.0000 atomic %, the content P(M) being obtained by energy dispersive X-ray analysis during line scanning in the range of 0.85d to 1.15d from the outline of the cross section of the toner particle toward the center of the cross section in a direction perpendicular to the outline, where d is the thickness of the shell (nm); and

[0018] According to nanoindentation measurement of the toner, the surface storage elastic modulus of the toner under a load of 30 μN at 25° C. is 6.50 GPa to 12.00 GPa.

[0019] Effects of the Invention

[0020] Thus, the present disclosure can provide a toner that exhibits excellent long-term developability by suppressing shell peeling while exhibiting maintenance and improvement of low-temperature fixability. Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION

[0021] In addition, in the present disclosure, unless otherwise specified, the expression "from XX to YY" or "XX to YY" indicating a numerical range refers to a numerical range including a lower limit and an upper limit as endpoints. When the numerical range is set in segments, the upper and lower limits of each numerical range can be combined in any combination.

[0022] The present disclosure relates to a toner, comprising toner particles, the toner particles comprising:

[0023] a core particle comprising a resin component,

[0024] a shell covering the surface of the core particle, and

[0025] Polyvalent metals, among which

[0026] The resin component comprises a polyester resin;

[0027] The shell comprises an amino resin;

[0028] In an electron image of a cross section of a toner particle taken using a transmission electron microscope,

[0029] The content P(M) of the polyvalent metal is 0.0010 to 2.0000 atomic %, the content P(M) being obtained by energy dispersive X-ray analysis during line scanning in the range of 0.85d to 1.15d from the outline of the cross section of the toner particle toward the center of the cross section in a direction perpendicular to the outline, where d is the thickness of the shell (nm); and

[0030] According to nanoindentation measurement of the toner, the surface storage elastic modulus of the toner under a load of 30 μN at 25° C. is 6.50 GPa to 12.00 GPa.

[0031] In the toner, a polyvalent metal is present at and near the core particle / shell interface, and the adhesion between the core particle and the shell is improved. Thus, even in the case where the surface storage elastic modulus of the toner having soft core particles showing low-temperature fixability is high, the adhesion between the core particle and the shell is high, and shell peeling can be suppressed. For a long-life development system, this can meet high expectations for toner developability while maintaining low-temperature fixability.

[0032] The present inventors consider that the reason why this effect is obtained by the toner is as follows.

[0033] In order to meet the high expectations for toner developability in a long-life development system, the surface storage elastic modulus of the toner under a load of 30 μN at 25° C. must be 6.50 GPa to 12.00 GPa in nanoindentation measurement of the toner. The storage elastic modulus of the toner surface indicates the storage elastic modulus of the outermost layer of the toner, and the inventors' studies have shown that it is correlated with development durability.

[0034] As described above, since the toner repeatedly receives stress from components such as a developing roller and a developing blade during development, the toner is broken and crushed. For the purpose of charging assistance and fluidity improvement, inorganic or organic fine particles called external additives may also be optionally added to the toner externally.

[0035] By making the surface storage elastic modulus 6.50 GPa or more, the occurrence of toner cracking and crushing is suppressed even when stress is repeatedly applied from the outside. In addition, since the external additive functions effectively for a long time, a toner having excellent development durability is provided.

[0036] By making the aforementioned surface storage elastic modulus 12.00 GPa or less, the external additive can be appropriately fixed and the colorant will be resistant to deformation, and because the external additive works effectively for a long time, a colorant with excellent development durability and capable of suppressing image defects, i.e., fogging and development streaks is provided.

[0037] The surface storage elastic modulus is preferably from 6.80 GPa to 11.60 GPa. By satisfying this range, a toner having further better development durability is provided.

[0038] The surface storage elastic modulus under a load of 30 μN can be controlled using the glass transition temperature Tg and acid value of the resin at the toner surface, and using the amount of metal ions at and near the core particle / shell interface.

[0039] The shell contains an amino resin in order to satisfy the above-mentioned requirements for the developing property of the toner.

[0040] The amino resin can be exemplified by melamine resin, guanamine resin, aniline resin, urea resin, polyurethane resin, sulfonamide resin, polyimide resin, and derivatives of these resins. The amino resin is preferably a thermosetting resin.

[0041] Suitable examples of thermosetting monomers that can be used for the amino resin are methylolmelamine, hexamethylolmelamine, melamine, methylolated urea (specifically, for example, dimethyloldihydroxyethylene urea), urea, benzoguanamine, acetoguanamine, and spiroguanamine.

[0042] The amino resin is more preferably at least one selected from the group consisting of melamine resins, urea resins, guanamine resins, and aniline resins, and melamine resins are more preferred.

[0043] The melamine resin is preferably a methylolmelamine resin, a hexamethylolmelamine resin, or a methoxymethylolmelamine resin, and hexamethylolmelamine resin is more preferred.

[0044] Thermosetting resins are obtained by subjecting one or more thermosetting monomers to a crosslinking reaction. The thermosetting monomer is a monomer having crosslinking properties. For example, when a thermosetting resin is obtained by three-dimensionally connecting the same monomers via "-CH2-", the monomer corresponds to a thermosetting monomer.

[0045] Thermosetting resins show excellent heat resistance and are resistant to deformation, and as a result, it is considered that when a thermosetting resin is used in a shell, the toner is resistant to deformation even when external strain is applied, and image defects of fogging and development streaks can be suppressed.

[0046] It is considered that the melamine resin in particular, since it is a polycondensate of melamine in which three amino groups are bonded to a triazine skeleton, provides an even stronger three-dimensional network structure.

[0047] In addition, the surface storage elastic modulus of the toner under a load of 50 μN at 25° C. is preferably 0.20 GPa to 12.00 GPa according to nanoindentation measurement of the toner. 0.30 GPa to 11.80 GPa is more preferred.

[0048] Nanoindentation measurement using a 50 μN load measures viscoelasticity in a region closer to the core of the toner particle than measurement using a 30 μN load. By making the surface storage elastic modulus of the toner particle at 50 μN within the above range, a toner showing excellent low temperature fixability, less fixing damage, and high development durability is provided. The surface storage elastic modulus at a 50 μN load can be controlled using the Tg and acid value of the resin in the core particle and the amount of metal ions.

[0049] The average value of the shell thickness is 1.0 nm to 30.0 nm. In the toner fixing step, heat and pressure from a member such as a fixing roller are applied to fix the toner on paper. A toner having excellent low-temperature fixability is obtained by making the shell thickness 30.0 nm or less.

[0050] Since stress is repeatedly applied to the toner during development, cracking and crushing of the toner occurs. Making the shell thickness 1.0 nm or more provides a toner that suppresses toner degradation. The average value of the shell thickness is 1.1 nm to 29.0 nm.

[0051] The entire surface of the core particle is not necessarily covered with the shell, and there may be a portion where the core particle is partially exposed.

[0052] In order to achieve both low-temperature fixability and high development durability in a toner exhibiting low-temperature fixability, it is important to improve core particle / shell adhesion, and as a result, a polyvalent metal is necessary.

[0053] In the electron image of the cross section of the colorant particle taken using a transmission electron microscope, the content P(M) of the polyvalent metal is 0.0010 to 2.0000 atomic %, and the content P(M) is obtained by energy dispersive X-ray analysis during line scanning in the range of 0.85d to 1.15d from the outline of the cross section of the colorant particle toward the center of the cross section in a direction perpendicular to the outline, where d is the thickness of the shell (nm).

[0054] Using d (nm) as the shell thickness, the range of 0.85d to 1.15d from the outline of the cross section of the toner particle toward the center of the cross section in a direction perpendicular to the outline represents the core particle / shell interface and the vicinity of the interface.

[0055] It is considered that in the toner particles satisfying the above, the shell and core particles are fixed to each other by non-covalent bonds due to the polyvalent metal. By making P(M) 0.0010 atomic % or more, the core particles can be satisfactorily adhered to the shell, and the shell peeling against external force can be suppressed.

[0056] By making P(M) 2.0000 atomic % or less, due to moderate fixing, the impact force is dissipated due to the display of a certain viscosity, and thus a toner resistant to cracking is provided. P(M) is preferably 0.0012 atomic % to 1.9400 atomic %. P(M) can be controlled by using the amount of polyvalent metal ions added.

[0057] The polyvalent metal is preferably at least one selected from the group consisting of Al, Ca, and Mg. These metals can be used alone, or multiple combinations can be used. These metals are divalent or higher metals, and strengthen the crosslinking between the core and the shell. At least one selected from the group consisting of Ca and Al with a small ionic radius is more preferred, and Al as a trivalent metal is further more preferred.

[0058] Ca and Al having small ionic radius strongly attract crosslinking segments in the core and shell, resulting in stronger crosslinking and providing a toner with high adhesion. In addition, since the crosslinking points between the core and the shell increase due to the trivalent metal, stronger crosslinking is provided and a toner with high adhesion is provided.

[0059] Preferably, the multivalent metal is Mg derived from magnesium hydroxide, Mg derived from magnesium chloride, or Al derived from aluminum sulfate.

[0060] By adding such metal salts as aggregating agents in the emulsion aggregation method, or adding them to the aqueous medium in the dissolution suspension method, or adding them to the aqueous medium of the core particle dispersion, the desired polyvalent metal can be contained at or near the core particle / shell interface.

[0061] In order to improve the adhesion with the shell resin through the above interaction, it is an essential requirement that the resin component of the core particle contains a polyester resin. The polyester resin is preferably a polycondensate between an alcohol component and a carboxylic acid component.

[0062] When a polyester resin is used in the resin component of the core particle, the polyester resin is oriented to the outermost surface. When a water-soluble salt of a divalent or higher metal is added in a state where the polyester resin is present at the outermost surface, the water-soluble metal salt dissolves in the aqueous medium, thereby providing divalent or higher metal ions.

[0063] The polyester resin contains carboxyl groups. It is believed that the divalent or higher metal ions are coordinated with the carboxyl groups in the polyester resin. When an amino resin is used in the shell, the nitrogen element forms a non-covalent bond with the metal ions coordinated with the carboxyl groups in the polyester resin, so that the core particle / shell adhesion can be improved due to intermolecular interactions.

[0064] This improvement in adhesion enables suppression of shell peeling even during long-term use. Suppression of shell peeling provides a toner that exhibits excellent durability and also exhibits long-term suppression of image defects of fogging and streaking.

[0065] The resin component of the core particle preferably contains 50.0% by mass or more of a polyester resin in the resin component. When the polyester resin is 50.0% by mass or more of the resin component of the core, the adhesion between the core and the shell is improved, and even during long-term use, shell peeling is suppressed. 55.0% by mass or more is more preferred, and 60.0% by mass or more is further more preferred. There is no particular restriction on the upper limit, but 98.0% by mass or less is preferred, and 95.0% by mass or less is more preferred.

[0066] For example, polyester resins, polycarbonate resins, phenol resins, epoxy resins, polyamide resins, cellulose resins, and styrene-acrylic resins may be used for the resin component of the core particles.

[0067] The alcohol component can be exemplified by ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butene glycol, octenyl glycol, cyclohexenedimethanol, hydrogenated bisphenol A, ethylene oxide adduct of bisphenol A, and propylene oxide adduct of bisphenol A.

[0068] Polycarboxylic acids can be exemplified by aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid, and their anhydrides; alkyl dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, and their anhydrides; succinic acid substituted by an alkyl or alkenyl group having 6 to 18 carbons, and its anhydride; and unsaturated dicarboxylic acids such as fumaric acid, maleic acid, and citraconic acid, and their anhydrides.

[0069] Resin component of core particles

[0070] The resin component of the core particles should contain a polyester resin, and may contain other resins in combination with the resin.

[0071] The following resins are provided as examples: for example, homopolymers of styrene and its substituents such as polystyrene, polyparachlorostyrene, and polyvinyltoluene; for example, styrene-based copolymers such as styrene-parachlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylate copolymers, styrene-methacrylate copolymers, styrene-α-chloromethylmethacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; and polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum resins.

[0072] The resin component of the core particle preferably contains a styrene-acrylic resin in addition to the polyester resin. The content of the styrene-acrylic resin in the resin component is preferably 2.0% by mass to 50.0% by mass, and more preferably 5.0% by mass to 45.0% by mass.

[0073] From the viewpoint of the stability of the triboelectric charge, the acid value of the polyester resin is preferably 1 mgKOH / g to 50 mgKOH / g. The acid value can be made within the above range by adjusting the type and compounding amount of the monomer used for the resin. Specifically, the acid value can be controlled by adjusting the molecular weight and the alcohol monomer component ratio / acid monomer component ratio in the resin production.

[0074] A crystalline polyester resin may also be used as the resin component in the core particles.

[0075] Colorants

[0076] Colorants may be used in toners.

[0077] The colorant can be exemplified as follows.

[0078] The black colorant can be exemplified by carbon black and can be exemplified by a colorant obtained by color mixing using a yellow colorant, a magenta colorant, and a cyan colorant to obtain black. Pigments can be used alone for the colorant; however, from the viewpoint of the quality of a full-color image, the use of a combination of dyes / pigments brings improved clarity and is therefore more preferred.

[0079] Magenta pigments can be exemplified by the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1 , 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, and 282; CI Pigment Violet 19; and CI Vat Red 1, 2, 10, 13, 15, 23, 29, and 35.

[0080] Magenta dyes can be exemplified by the following: oil-soluble dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, and 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, and 27; and CI Disperse Violet 1. Basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, and 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, and 28.

[0081] Cyan pigments can be exemplified by the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, and 17; CI Vat Blue 6; CI Acid Blue 45; and copper phthalocyanine pigments in which 1 to 5 phthalimidomethyl groups are substituted on the phthalocyanine skeleton.

[0082] The cyan dye may be exemplified by CI Solvent Blue 70.

[0083] The yellow pigment can be exemplified by the following: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, and 185; and CI Vat Yellow 1, 3, and 20.

[0084] The yellow dye may be exemplified by CI Solvent Yellow 162.

[0085] The amount of the colorant used is preferably 0.1 parts by mass to 30.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0086] wax

[0087] The toner preferably contains wax. The wax can be exemplified by the following:

[0088] For example, hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax, and block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and waxes obtained by partial or complete deacidification of fatty acid esters such as deacidified carnauba wax.

[0089] Other examples are as follows: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassinoic acid, eleostearic acid, and octadecatetraenoic acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol, and myricol; polyols such as sorbitol; esters between fatty acids such as palmitic acid, stearic acid, behenic acid, or montanic acid and alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol, or myricol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauramide; methylene bisstearamide, ethylene biscaproamide, ethylene bislauramide, and hexamethylene bisstearamide, etc. Saturated fatty acid bisamides; unsaturated fatty acid amides such as ethylenebisoleamide, hexamethylenebisoleamide, N,N′-dioleyl adipamide, and N,N′-dioleyl sebacamide; aromatic bisamides such as meta-xylene bisstearamide and N,N′-distearylisophthalamide; fatty acid metal salts (commonly called metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes obtained by grafting aliphatic hydrocarbon waxes with vinyl monomers such as styrene or acrylic acid; partial esterification products between fatty acids and polyols such as behenyl alcohol monoglyceride; and hydroxyl-containing methyl ester compounds obtained by hydrogenation of vegetable oils.

[0090] Among these waxes, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax are preferred from the viewpoint of improving low-temperature fixability.

[0091] The content of the wax is preferably 0.5 parts by mass to 25.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0092] From the viewpoint of coexistence of toner storability and its hot offset resistance, the peak temperature of the maximum endothermic peak of the wax existing in the temperature range of 30°C to 200°C in the endothermic curve during temperature increase measured by a differential scanning calorimeter (DSC) is preferably 50°C to 110°C.

[0093] Charge control agent

[0094] A charge control agent may also be optionally contained in the toner. Known charge control agents can be used for the charge control agent, but a metal compound of an aromatic carboxylic acid which is colorless, provides a high toner charging speed, and can maintain a stable and certain charge amount is particularly preferred.

[0095] Negatively charged charge control agents can be exemplified by the following: salicylic acid metal compounds, naphthoic acid metal compounds, dicarboxylic acid metal compounds, polymer compounds having sulfonic acid or carboxylic acid at the side chain position, polymer compounds having sulfonates or sulfonates at the side chain position, polymer compounds having carboxylates or carboxylates at the side chain position, boron compounds, urea compounds, silicon compounds, and calixarene.

[0096] The charge control agent may be internally added to the toner particles, or may be externally added to the toner particles.

[0097] The amount of the charge control agent added is preferably 0.2 parts by mass to 10 parts by mass relative to 100 parts by mass of the binder resin.

[0098] From the viewpoint of obtaining stable images over a long period of time, the toner may be used in the form of a two-component developer obtained by mixing with a magnetic carrier.

[0099] For example, the following known magnetic carriers can be used as the magnetic carrier here: for example, magnetic bodies such as surface-oxidized iron powder; unoxidized iron powder; metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth particles, and their alloy particles, oxide particles, and ferrites; and magnetic body dispersion resin carriers (referred to as resin carriers) comprising a magnetic body and a binder resin that retains the magnetic body in a dispersed state.

[0100] Any production method can be used for the production method of toner particles. Examples are methods in which toner is produced directly in a hydrophilic medium, for example, emulsion aggregation, dissolution suspension, and suspension polymerization. A pulverization method can also be used, and the toner obtained by the pulverization method can be thermally spheroidized.

[0101] Among them, the above-mentioned effect is easily obtained with a toner produced by emulsion aggregation. The reason is that during the production step, the polyester resin is promoted to appear at the surface of the toner particles. This is due to the following: in the emulsion aggregation method, core particles are formed by coalescence of aggregated particles; carboxyl groups, which are contained in the polyester resin and form segments bonded to the shell, are easily exposed at the surface; and the adhesion between the core and the shell is made stronger.

[0102] A method for producing toner particles by emulsion aggregation is provided below as an example.

[0103] Dispersion preparation steps

[0104] The preparation of a dispersion liquid of resin particles for the purpose of producing resin particles to be used as core particles will be described. The resin particle dispersion liquid can be prepared, for example, as described below.

[0105] In the case where the resin in the resin particles is a homopolymer or copolymer of a vinyl monomer (vinyl resin), the ionic surfactant-supported dispersion of the resin particles of the homopolymer or copolymer of the vinyl monomer (vinyl resin) is prepared by, for example, emulsion polymerization or seed polymerization of the vinyl monomer in an ionic surfactant.

[0106] In the case where the resin in the resin particles is a resin other than a vinyl resin, for example, a polyester resin, the resin is mixed in an aqueous medium in which an ionic surfactant or a polyelectrolyte is dissolved.

[0107] Then, the solution is heated to a temperature higher than the melting point or softening point to dissolve the solution, and a dispersion in which the resin particles are dispersed via an ionic surfactant is prepared using a dispersion device having a strong shearing force such as a homogenizer.

[0108] The dispersing means is not particularly limited, and can be exemplified by per se known dispersing devices such as a rotary shearing type homogenizer and a media-based ball mill, a sand mill, and a Dynamill.

[0109] Phase inversion emulsification can also be used for the dispersion preparation method. The phase inversion emulsification method is a method in which a binder resin is dissolved in an organic solvent and a neutralizer and / or a dispersion stabilizer are optionally added; an aqueous solvent is added dropwise while stirring to obtain emulsified particles; and then the organic solvent in the resin dispersion is removed to obtain an emulsion. The order of inputting the neutralizer and / or the dispersion stabilizer during this process may be changed.

[0110] The number average particle size of the resin particles is generally 1 μm or less and preferably 0.01 to 1.00 μm. When the number average particle size is within the above range, a narrow particle size distribution can be provided for the toner, and the generation of free particles can be suppressed. In addition, the unevenness of the distribution of the resin particles between the regulators is reduced, excellent dispersion of the components in the toner is provided, and the performance and reliability are hardly scattered.

[0111] As required, a colorant particle dispersion can be prepared. The colorant particle dispersion is a colorant particle dispersion in which at least colorant particles are dispersed in a dispersant. The number average particle diameter of the colorant particles is preferably below 0.5 μm and more preferably below 0.2 μm. When the number average particle diameter is below 0.5 μm, diffuse reflection of visible light can be prevented, and excellent tinting power, color reproducibility, and OHP transparency are provided in addition. In addition, the uneven distribution between the toners caused by the colorant is minimized, providing excellent colorant dispersion in the toner, and performance and reliability are almost not discrete.

[0112] As required, a wax particle dispersion can be prepared. The wax particle dispersion is a wax particle dispersion in which at least wax particles are dispersed in a dispersant. The number average particle size of the wax particles is preferably 2.0 μm or less and more preferably 1.0 μm or less. When the number average particle size is within the above range, uneven distribution between toners caused by the wax is minimized, providing excellent wax dispersion in the toner, and little dispersion in performance and reliability.

[0113] The colorant particles+resin particles+wax particles combination is not particularly limited and may be freely selected appropriately according to purpose.

[0114] In addition to the resin particle dispersion and the colorant particle dispersion and the wax particle dispersion, a particle dispersion obtained by dispersing appropriately selected particles in a dispersant may be mixed.

[0115] The particles contained in the particle dispersion can be appropriately selected according to the purpose without particular limitation, and examples here are internal additive particles, charge control agent particles, inorganic particles, and grinding material particles. In addition, these particles can be dispersed in a resin particle dispersion and / or a colorant particle dispersion.

[0116] For example, the dispersant present in the resin particle dispersion, the colorant particle dispersion, the wax fine dispersion, and the particle dispersion may be, for example, an aqueous medium containing a polar surfactant.

[0117] The aqueous medium can be exemplified by alcohol and can be exemplified by water, for example, distilled water, and deionized water, etc. These can be used alone or in combination of two or more. The content of the polar surfactant cannot be unconditionally specified and can be appropriately selected according to the purpose.

[0118] The polar surfactant may be exemplified by anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps, and cationic surfactants such as amine salts and quaternary ammonium salts.

[0119] The anionic surfactant can be specifically exemplified by sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium alkylnaphthalenesulfonate, and sodium dialkylsulfosuccinate.

[0120] Specific examples of the cationic surfactant include alkylbenzenedimethylammonium chloride, alkyltrimethylammonium chloride, and distearylammonium chloride. These may be used alone or in combination of two or more.

[0121] Polar surfactants can also be used in combination with non-polar surfactants. Examples of non-polar surfactants include nonionic surfactants such as polyethylene glycol, alkylphenol / ethylene oxide adducts, and polyols. The content of the colorant particles is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the resin component in the aggregated particle dispersion when the aggregated particles are formed.

[0122] The content of the wax particles is preferably 0.5 parts by mass to 25 parts by mass and more preferably 5 to 20 parts by mass relative to 100 parts by mass of the resin component in the aggregated particle dispersion when the aggregated particles are formed.

[0123] It is also possible to add the charge control particles and the resin particles after the formation of the aggregated particles in order to perform fine control of the chargeability of the resulting toner.

[0124] The measurement of the particle diameters of the resin particles, the colorant particle dispersion, the wax microdispersion, the particle dispersion, and the like was performed using an LA-920 laser diffraction / scattering particle size distribution analyzer from Horiba, Ltd.

[0125] Aggregation Step

[0126] The aggregation step of forming aggregated particles is a step of forming aggregated particles containing resin particles, colorant particles, wax particles, and the like in an aqueous medium containing at least resin particles and optionally colorant particles, wax particles, and the like.

[0127] Aggregated particles can be formed, for example, in an aqueous medium by adding a pH adjuster, an aggregating agent, and a stabilizer to an aqueous medium, mixing, and appropriately applying, for example, temperature, mechanical power, and the like.

[0128] The pH adjuster can be exemplified by bases such as ammonia and sodium hydroxide, and can be exemplified by acids such as nitric acid and citric acid. The aggregating agent can be exemplified by salts of monovalent metals such as sodium and potassium; salts of divalent metals such as calcium and magnesium; salts of trivalent metals such as iron and aluminum; and alcohols such as methanol, ethanol, and propanol.

[0129] The stabilizer can be mainly exemplified by the polar surfactant itself, and can be exemplified by the aqueous medium containing it. For example, when the polar surfactant contained in each particle dispersion is anionic, a cationic one can be selected as the stabilizer.

[0130] The addition and mixing of the aggregating agent etc. are preferably carried out at a temperature below the glass transition temperature of the resin present in the aqueous medium. When mixing is carried out using this temperature condition, aggregation is carried out under stable conditions. For example, a mixing device, a homogenizer, and a mixer etc. known per se can be used for mixing.

[0131] Aggregated particles having a core / shell structure can also be obtained in the aggregation step, wherein a shell is formed on the surface of the core aggregated particles by attaching the second resin particles to the aggregated particle surface using a resin particle dispersion containing the second resin particles to form a coating layer (shell). The second resin particles used here may be the same as or different from the resin particles constituting the core aggregated particles. The aggregation step can be repeated by being divided into a plurality of stages.

[0132] Fusion Steps

[0133] The fusing step is a step of fusing the obtained aggregated particles by heating them. Before entering the fusing step, for example, a pH adjuster, a polar surfactant, a nonpolar surfactant, etc. may be appropriately added to prevent the toner particles from being melt-adhered to each other.

[0134] The heating temperature should be at least the glass transition temperature of the resin contained in the aggregated particles (when there are two or more resins, the glass transition temperature of the resin with the higher or highest glass transition temperature) and lower than the decomposition temperature of the resin. Therefore, the heating temperature will vary depending on the type of resin and therefore cannot be specified unconditionally; however, it is usually the glass transition temperature of the resin contained in the aggregated particles and 140° C. or less. Heating can be performed using a known heating device or heating instrument.

[0135] Regarding the duration of fusion, a shorter time will suffice at a higher heating temperature, while a longer time will be required at a lower heating temperature. Therefore, the duration of fusion cannot be unconditionally specified because it depends on the heating temperature; however, it is generally 30 minutes to 10 hours.

[0136] The toner particles obtained by performing these individual steps can be recovered by solid-liquid separation, followed by washing and drying under appropriate conditions, etc., using a known method.

[0137] External Addition Steps

[0138] The toner particles can be used as, for example, a toner. External additives may be attached to the toner particle surfaces for the purpose of imparting various characteristics to the toner. The toner preferably further includes an external additive.

[0139] From the viewpoint of durability when added to toner particles, the particle size of the external additive is preferably one tenth or less of the average particle size of the toner particles before the external additive is applied. The external additive can be exemplified by the following:

[0140] Examples include metal oxides such as aluminum oxide, titanium oxide, strontium titanate, cerium oxide, magnesium oxide, chromium oxide, tin oxide, and zinc oxide; nitrides such as silicon nitride; carbides such as silicon carbide; inorganic metal salts such as calcium sulfate, barium sulfate, and calcium carbonate; metal salts of fatty acids such as zinc stearate and calcium stearate; and carbon black and silicon dioxide. Among them, silicon dioxide is preferred.

[0141] The content of the external additive is preferably 0.01 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass relative to 100 parts by mass of the toner particles. One type of external additive may be used alone, or two or more types may be used in combination. From the viewpoint of charge stability, it is preferred to use an external additive that has been subjected to a surface hydrophobic treatment.

[0142] Examples of the hydrophobic treatment agent include silane coupling agents such as methyltrimethoxysilane, methyltriethoxysilane, isobutyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, and hexamethylenedisilazane.

[0143] The following describes the measurement methods of various properties.

[0144] Measurement of Surface Viscoelasticity of Toner

[0145] A TI-950 System friction indenter (Hysitron Corporation) is used as a measuring instrument for measuring the surface storage elastic modulus of the toner by the nanoindentation method.

[0146] Regarding the measurement sample, operating under a 25° C. environment, the toner was adhered to the tip of a cotton swab (Johnson & Johnson), and 0.1 mg of the toner was spread on a 1 cm×1 cm silicon wafer to obtain a sample to be used.

[0147] The sample was mounted on a sample chuck and operated at room temperature (25° C.), using nanoindentation conditions and starting the measurement using a Berkovich diamond indenter (TI-0039, angle: 142.3°) (Hysitron Corporation).

[0148] Before starting the measurement, focus is established on the measurement sample and, importantly, the measurement is performed under uniform focus conditions.

[0149] Use the microscope software to measure the focus on the sample. Focus the objective lens from 5x to 20x and 50x at a time. After this, adjust with the 50x objective lens.

[0150] Then, the measurement space and load force were calibrated using an Al plate attachment. The Z-axis alignment of the indenter was performed by performing a positional alignment between the tip of the indenter and the focal position of the microscope camera.

[0151] Then, the tip of the indenter is moved onto the silicon wafer loaded with the toner and the microscope is focused on the toner as a measurement target.

[0152] After these calibrations, measurements were performed using the following conditions.

[0153] The pressure head load condition is 30 μ N, and the load is applied to 30 μ N from 0 μ N with 0.5 μ N / s. Subsequently, the nano viscoelasticity is measured by applying vibration in the following order using the following frequency and time: 3 seconds at 3.0 Hz, 5 seconds at 30 Hz, 15 seconds at 150 Hz, and 40 seconds at 301.5 Hz. The frequency change is accompanied by the application of a second of stable time between each frequency. In this process, 200 points of 100 pts / sec are used for data map counting, and its average value is calculated.

[0154] The measurement was started, and calculation was performed using the frequency (Hz) as the horizontal axis and the storage elastic modulus (GPa) and the loss elastic modulus (GPa) as the vertical axis.

[0155] This measurement is performed on 30 particles of the toner and the average value is used.

[0156] Always measure each particle with a clean indenter (XY-axis alignment).

[0157] The measurement using the load condition of 50 μN was performed in the same manner as the load condition of 30 μN, except that the load was applied from 0 μN to 50 μN at 0.5 μN / s.

[0158] Separation of toner particles from toner

[0159] When toner particles are used as a sample, toner particles obtained by removing an external additive from a toner by using the following method may also be used.

[0160] (1) 5 g of toner to which an external additive has been externally added is introduced into a sample bottle and 200 mL of methanol is added. A few drops of a surfactant are added as needed. "Contaminon N" (a 10% by mass aqueous solution of a neutral pH 7 detergent for washing precision measuring instruments including a nonionic surfactant, an anionic surfactant, and an organic builder, from Wako Pure Chemical Industries, Ltd.) can be used as a surfactant.

[0161] (2) The external additives were separated by dispersing the sample for 5 minutes using an ultrasonic cleaner.

[0162] (3) The toner particles were separated from the external additives by suction filtration (10 μm membrane filter).

[0163] (4) The above (2) and (3) are performed three times in total.

[0164] Toner particles from which external additives have been removed can be obtained from the toner using this process.

[0165] Measurement of Metal Amount in Cross Section of Toner Particles

[0166] The polyvalent metal content is measured using the following method and a transmission electron microscope (TEM) from an electron image of a cross section of a toner particle.

[0167] In order to prepare the measurement sample, the toner particles were mixed with a visible light curable embedding resin (D-800, Nisshin EM Co., Ltd.) and press-formed into a disc shape with a diameter of 7.9 mm and a thickness of 1.0 ± 0.3 mm using a tablet forming machine under an environment of 25°C to obtain a sample embedded with the toner particles. The press-forming was performed under the conditions of 35 MPa and 60 seconds. A thin sheet sample with a film thickness of 100 nm was cut out from the sample at a slicing speed of 0.6 mm / s using an ultramicrotome equipped with a diamond cutter (EMUC7, Leica).

[0168] The toner particle cross sections were observed at a magnification of 500,000 times using these samples and a transmission electron microscope (TEM) (Model JEM2800, JEOL Ltd.) under the conditions of an accelerating voltage of 200 keV and an electron beam probe size of 1 mm. The cross sections were observed for which the major diameter was ±10% of the weight average particle diameter (D4) of the toner particles under observation.

[0169] Using an energy dispersive X-ray analyzer (EDS: NSS, Thermo Electron Corporation), a spectrum of constituent elements is collected in the obtained toner particle cross section. The range of R given in the following formula (1) is used for the range of spectrum collection.

[0170] The spectrum of the polyvalent metal P (M) is collected by line scanning from the outline of the cross section of the toner particle having a shell thickness d (nm) toward the center portion of the cross section in a direction perpendicular to the outline.

[0171] The shell thickness d in this measurement is measured as described below in “Measurement of average value of shell thickness.” The average value of the shell thickness at four locations in the toner particle as the measurement target is used as d (nm).

[0172] The shell is dyed by using osmium tetroxide which selectively dyes only the shell in the toner particles to be distinguished from the core particles.

[0173] Formula (1) 0.85d≤R≤1.15d

[0174] For the value in the case where the polyvalent metal peak P(M) is the maximum value within the range of formula (1), quantitative analysis is performed from the obtained spectrum by the Cliff-Lorimer method, and the polyvalent metal content P(M) atomic % is calculated. P(M) atomic % is the atomic weight fraction when all elements detected during the analysis are taken as 100%.

[0175] The Cliff-Lorimer method uses an energy dispersive X-ray analyzer (EDS: NSS, Thermo Electron Corporation) and performs calculations using a qualitative sensitivity of 5, an overvoltage of 1.5 keV, and an oxygen atom number of 0 as analysis conditions, and performs matrix correction to correct for the effects of coexisting elements.

[0176] This measurement is performed on cross sections of 20 toner particles, and the resulting arithmetic mean is used.

[0177] Measurement of the average shell thickness

[0178] To prepare a measurement sample, the toner particles were mixed with a visible light curable embedding resin (D-800, Nisshin EM Co., Ltd.) and press-formed into a disk shape having a diameter of 7.9 mm and a thickness of 1.0 ± 0.3 mm using a tablet forming machine under an environment of 25° C. to obtain a sample in which the toner particles were embedded. The press-forming was performed using conditions of 35 MPa and 60 seconds.

[0179] A thin plate-like sample with a film thickness of 100 nm was cut from the sample at a slicing speed of 0.6 mm / s using an ultramicrotome (EMUC7, Leica) equipped with a diamond cutter. The resulting sample was stained with osmium tetroxide. This process resulted in selective staining of only the shell in the toner particles.

[0180] Then, the cross section in the obtained thin-section sample was imaged at a magnification of 500,000 times using a transmission electron microscope (TEM) (Model JEM2800, JEOL Ltd.) and conditions of an accelerating voltage of 200 keV and an electron beam probe size of 1 mm. The shell thickness was measured by analyzing the TEM image using image analysis software.

[0181] Specifically, two orthogonal straight lines are drawn at approximately the center of the cross section of the toner particle, and the shell thickness is measured at each of four positions where these two straight lines intersect the shell. The arithmetic mean of the thicknesses measured at the four positions is taken as the shell thickness of the specific toner particle. The shell thickness is measured for each of 20 toner particles, and the number average of the measured thicknesses is used as the evaluation value (average shell thickness) of the toner as the measurement target.

[0182] Method for measuring weight average particle size (D4) of toner particles

[0183] The weight average particle size (D4) of the toner particles is determined using a precision particle size distribution measuring instrument "Coulter Counter Multisizer 3" (registered trademark, Beckman Coulter, Inc.) which operates based on the pore resistance method and is equipped with a 100 μm orifice tube, by measuring in 25,000 channels with an effective measurement channel number, and using dedicated software attached for setting measurement conditions and analyzing measurement data, i.e., "Beckman Coulter Multisizer 3 Version 3.51" (Beckman Coulter, Inc.).

[0184] The electrolyte aqueous solution used for measurement is prepared by dissolving special grade sodium chloride in deionized water to obtain a concentration of about 1 mass %, and for example, "ISOTON II" (Beckman Coulter, Inc.) can be used.

[0185] Prior to measurement and analysis, the dedicated software was set as follows.

[0186] In the "Change Standard Measurement Method (SOM)" screen of the dedicated software, set the total count in the technique mode to 50,000 particles; set the number of measurements to 1; and set the Kd value to the value obtained using "Standard Particles 10.0 μm" (Beckman Coulter, Inc.). The threshold and noise level are automatically set by pressing the Threshold / Noise Level Measurement button. In addition, set the current to 1,600 μA; set the gain to 2; set the electrolyte solution to ISOTON II; and check the box to rinse the orifice tube after measurement.

[0187] In the "Pulse to Size Conversion Settings" screen of the dedicated software, set the element spacing to logarithmic size; set the size elements to 256 size elements; and set the size range to 2 μm to 60 μm.

[0188] The specific measurement process is as follows.

[0189] (1) About 200 mL of the above electrolyte aqueous solution was introduced into a 250 mL round-bottom glass beaker dedicated to Multisizer 3, and placed on the sample stage, and stirred counterclockwise at 24 rpm with a stirring rod. Dirt and bubbles in the nozzle were preliminarily removed by the "swept nozzle flushing" function of the dedicated software.

[0190] (2) About 30 mL of the electrolyte aqueous solution was introduced into a 100 mL flat-bottom glass beaker, and about 0.3 mL of the following dilution liquid was added thereto as a dispersant.

[0191] Dilution: A dilution prepared by diluting "Contaminon N" (a 10% by mass aqueous solution of a neutral pH 7 detergent for washing precision measuring instruments including a nonionic surfactant, an anionic surfactant, and an organic builder, from Wako Pure Chemical Industries, Ltd.) with deionized water three times (by mass)

[0192] (3) A predetermined amount of deionized water was introduced into a water tank of an ultrasonic disperser having a power output of 120 W and equipped with two oscillators (oscillation frequency = 50 kHz) configured so as to be 180° phase-shifted, and approximately 2 mL of Contaminon N was added to the water tank.

[0193] Ultrasonic Dispersion System Tetora 150 (NikkakiBiosCo.,Ltd.)

[0194] (4) The beaker in (2) is set in the beaker holding hole of the ultrasonic disperser, and the ultrasonic disperser is activated. The height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker is maximized.

[0195] (5) While irradiating the electrolyte aqueous solution in the beaker set according to (4) with ultrasonic waves, about 10 mg of toner is added in small amounts to the electrolyte aqueous solution and dispersed. The ultrasonic dispersion treatment is continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 15° C. to 40° C.

[0196] (6) The aqueous electrolyte solution containing the dispersed toner prepared in (5) above is dropped into the round bottom beaker set in the sample stage as described in (1) using a pipette, and adjusted to obtain a measurement concentration of about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.

[0197] (7) Analyze the measurement data and calculate the weight average particle size (D4) using the dedicated software set by the device. When the dedicated software is set to Graph / Volume %, the "Average Diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight average particle size (D4).

[0198] Method for measuring the acid value of resin

[0199] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid present in 1 g of a sample. The acid value of a resin is measured in accordance with JIS K0070-1992, and is specifically measured using the following procedure.

[0200] (1) Preparation of reagents

[0201] A phenolphthalein solution was obtained by dissolving 1.0 g of phenolphthalein in 90 mL of ethanol (95% by volume) and making up to 100 mL by adding deionized water.

[0202] 7g of special grade potassium hydroxide is dissolved in 5mL water, and is made into 1L by adding ethanol (95 volume %).It is introduced in the alkali-resistant container, avoids with for example, carbon dioxide contact, and is placed for 3 days, after this time, filters to obtain potassium hydroxide solution.The potassium hydroxide solution obtained is stored in the alkali-resistant container.When 25mL 0.1mol / L hydrochloric acid is introduced in the conical flask, add a few drops of phenolphthalein solution, and use potassium hydroxide solution to titrate, by the amount of potassium hydroxide solution required for neutralization, determine the factor of this potassium hydroxide solution.Prepare employed 0.1mol / L hydrochloric acid according to JIS K 8001-1998.

[0203] (2) Operation

[0204] (A) Main test

[0205] 2.0g sample is accurately weighed in a 200mL conical flask, and 100mL toluene / ethanol (2:1) mixed solution is added, and dissolved in 5 hours. A few drops of phenolphthalein solution are added as an indicator, and potassium hydroxide solution is used for titration. The titration end point is taken as the light red color of the indicator for about 30 seconds.

[0206] (B) Blank test

[0207] The same titration as in the above step was performed except that no sample was used (ie, only a toluene / ethanol (2:1) mixed solution was used).

[0208] (3) The acid value is calculated by substituting the obtained result into the following formula.

[0209] A=[(CB)×f×5.61] / S

[0210] Here, A: acid value (mgKOH / g); B: amount of potassium hydroxide solution added in the blank test (mL); C: amount of potassium hydroxide solution added in the main test (mL); f: factor of potassium hydroxide solution; and S: mass of the sample (g).

[0211] Measurement of glass transition temperature (Tg) of resin

[0212] The Tg of the resin is measured using a differential scanning calorimeter (DSC measuring instrument).

[0213] A "Q1000" differential scanning calorimeter (trade name, TA Instruments) was used as a differential scanning calorimeter, and the measurement was performed as follows according to ASTM D 3418-82. 3 mg of the measurement sample (resin) was accurately weighed. It was introduced into an aluminum pan, and an empty aluminum pan was used as a reference. After equilibration at 20° C. for 5 minutes, the measurement was performed at a heating rate of 10° C. / min in a temperature range of 20° C. to 180° C. The glass transition temperature was determined by the midpoint method.

[0214] Example

[0215] The present invention is described in more detail below using examples. The present invention is not limited by the following examples. Unless otherwise specifically stated, in all cases, the parts and % in the examples and comparative examples are based on mass.

[0216] Production of polyester resin 1 for core particles

[0217] The monomers were introduced in the amounts given in Table 1 into a reactor equipped with a nitrogen introduction tube, a water separation tube, a stirrer, and a thermocouple, and then 0.5 parts of dibutyltin were added as a catalyst relative to 100 parts of the total amount of the monomers. Then, the temperature was rapidly raised to 180° C. under a nitrogen atmosphere at normal pressure, followed by polycondensation while distilling off water and heating from 180° C. to 210° C. at a rate of 10° C. / hour.

[0218] Then, heating was performed to 210° C., and a reaction was performed while reducing pressure until a desired molecular weight was reached, to obtain a polyester resin 1.

[0219] <Production of Polyester Resins 2 to 5 for Core Particles>

[0220] Polyester resins 2 to 5 were prepared by the same production method as that of polyester resin 1 except that the raw materials were changed as shown in Table 1.

[0221] The unit of Tg is ° C. The abbreviations used in the table are expanded as follows.

[0222] TPA: Terephthalic acid

[0223] IPA: Isophthalic acid

[0224] TMA: trimellitic acid

[0225] BPA-PO: 2 mol propylene oxide adduct of bisphenol A

[0226] BPA-EO: 2 mol ethylene oxide adduct of bisphenol A

[0227] [Table 1]

[0228]

[0229] Production of Styrene-Acrylic Resins for Core Particles

[0230] While stirring, 80.0 parts of styrene, 20.0 parts of n-butyl acrylate, and 0.3 parts of hexanediol diacrylate were added to a reactor equipped with a stirrer, a thermometer, and a nitrogen inlet tube and heated to a temperature of 80°C.

[0231] Then, 2.0 parts of Perbutyl O (10-hour half-life temperature: 72.1° C. (NOF Corporation)) was added as a polymerization initiator and polymerization was performed for 5 hours to obtain a styrene-acrylic resin for core particles.

[0232] Production Example of Shell Dispersion Liquid 1

[0233] 300 parts of deionized water were added to a 1 L three-necked flask equipped with a thermometer and a stirring blade; dilute hydrochloric acid was added to adjust the pH to 4; and the temperature was maintained at 30° C. The monomers shown in Table 2 were added to the solution adjusted to pH 4 in the amounts shown in Table 2, and dispersed to obtain Shell Dispersion Liquid 1.

[0234] Production Examples of Shell Dispersions 2 to 5

[0235] Except that the monomer composition was changed as shown in Table 2, Shell Dispersions 2 to 5 were obtained in the same manner as in Production Example of Shell Dispersion 1.

[0236] [Table 2]

[0237] Shell dispersion monomer Add (portion) Shell dispersion 1 Hexamethylolmelamine 30.0 Shell dispersion 2 Benzoguanamine 50.0 Shell dispersion 3 aniline 50.0 Shell dispersion 4 Hydroxymethylated urea 70.0 Shell dispersion 5 phenol 30.0

[0238] Preparation of polyester resin particle dispersion

[0239] ·Polyester resin 1 200 parts

[0240] 500 parts of deionized water

[0241] These materials were introduced into a stainless steel container; heated to 95° C. on a hot bath and melted; and, while being thoroughly stirred at 7800 rpm using a homogenizer (Ultra-Turrax T50, IKA), the pH was made greater than 7.0 by adding 0.1 mol / L sodium bicarbonate.

[0242] Then, a polyester resin particle dispersion was obtained by gradually dropping a mixed solution of 3 parts of sodium dodecylbenzenesulfonate and 297 parts of deionized water while emulsifying and dispersing. When the particle size distribution of the polyester particle dispersion 1 was measured using a particle size distribution analyzer (LA-920, Horiba, Ltd.), the number average particle size of the contained polyester particles was 0.25 μm and no coarse particles exceeding 1 μm were observed.

[0243] Preparation of styrene-acrylic resin particle dispersion

[0244] 300 parts of xylene (boiling point 144° C.) were introduced into a flask which could be pressurized and could be placed under reduced pressure, the inside of the container was sufficiently replaced with nitrogen while stirring, and reflux was established by heating.

[0245] Under reflux, the following mixture was added:

[0246] ·88.50 parts of styrene

[0247] ·2.50 parts of methyl methacrylate

[0248] · 2-Hydroxyethyl Methacrylate 5.00 parts

[0249] ·Methacrylic acid 4.00 parts

[0250] ·Di-tert-butyl peroxide 2.00 parts

[0251] Then, polymerization was performed at a polymerization temperature of 175° C. and a pressure of 0.100 MPa for 5 hours during the reaction. Thereafter, a solvent removal process was performed under reduced pressure for 3 hours to remove xylene, and then pulverized to obtain a styrene-acrylic resin 1.

[0252] A styrene-acrylic resin particle dispersion was obtained in the same manner as in (Preparation of Polyester Resin Particle Dispersion) using styrene-acrylic resin 1 instead of polyester resin 1.

[0253] Preparation of wax particle dispersion

[0254] 500 parts of deionized water

[0255] · 250 parts of wax (hydrocarbon wax; the temperature at which the endothermic peak is the maximum = 77°C)

[0256] These materials were introduced into a stainless steel container; heated to 95° C. on a hot bath and melted; and, while being thoroughly stirred at 7800 rpm using a homogenizer (Ultra-Turrax T50, IKA), the pH was made greater than 7.0 by adding 0.1 mol / L sodium bicarbonate.

[0257] Then, while emulsifying and dispersing, a mixed solution of 5 parts of sodium dodecylbenzenesulfonate and 245 parts of deionized water was gradually added dropwise. When the particle size distribution of the wax particles in the wax particle dispersion was measured using a particle size distribution analyzer (LA-920, Horiba, Ltd.), the number average particle size of the wax particles contained was 0.35 μm and no coarse particles exceeding 1 μm were observed.

[0258] Preparation of Colorant Particle Dispersion 1

[0259] CI Pigment Blue 15:3 100 parts

[0260] · 5 parts of sodium dodecylbenzene sulfonate

[0261] 400 parts of deionized water

[0262] The aforementioned components were mixed and dispersed using a sand mill. When the particle size distribution of the colorant particles contained in the colorant particle dispersion was measured using a particle size distribution analyzer (LA-920, Horiba, Ltd.), the number average particle size of the contained colorant particles was 0.2 μm and coarse particles exceeding 1 μm were not observed.

[0263] Preparation of Colorant Particle Dispersion 2

[0264] CI Pigment Red 122 100 parts

[0265] · 5 parts of sodium dodecylbenzene sulfonate

[0266] 400 parts of deionized water

[0267] The aforementioned components were mixed and dispersed using a sand mill. When the particle size distribution of the colorant particles contained in the colorant particle dispersion was measured using a particle size distribution analyzer (LA-920, Horiba, Ltd.), the number average particle size of the contained colorant particles was 0.2 μm and coarse particles exceeding 1 μm were not observed.

[0268] Preparation of Colorant Particle Dispersion 3

[0269] ·CI Pigment Yellow 74 100 parts

[0270] · 5 parts of sodium dodecylbenzene sulfonate

[0271] 400 parts of deionized water

[0272] The aforementioned components were mixed and dispersed using a sand mill. When the particle size distribution of the colorant particles contained in the colorant particle dispersion was measured using a particle size distribution analyzer (LA-920, Horiba, Ltd.), the number average particle size of the contained colorant particles was 0.2 μm and coarse particles exceeding 1 μm were not observed.

[0273] Production of toner 1

[0274] Production of nuclear particles 1

[0275] · 450 parts of polyester resin particle dispersion

[0276] 50 parts of styrene-acrylic resin particle dispersion

[0277] · Colorant particle dispersion 1 50 parts

[0278] 50 parts of wax particle dispersion

[0279] ·5 parts of sodium dodecylbenzene sulfonate

[0280] The polyester resin particle dispersion, styrene-acrylic resin particle dispersion, wax particle dispersion, and sodium dodecylbenzenesulfonate were introduced into a reactor (a flask with a capacity of 1 liter, an anchor blade equipped with a baffle), and mixed until uniform. The colorant particle dispersion 1 was mixed separately in a 500 mL beaker until uniform, and was gradually added to the reactor while stirring to obtain a mixed dispersion. While stirring the obtained mixed dispersion, an aluminum sulfate aqueous solution having a solid content of 0.5 parts was added dropwise to form aggregated particles.

[0281] After completion of the dropwise addition, the inside of the system was replaced with nitrogen, and retention was performed at 50°C for 1 hour, and at 55°C for another 1 hour.

[0282] Then, heating was performed and maintained at 90°C for 30 minutes. Subsequently, cooling was performed to 63°C and then maintained for 3 hours to form agglomerated particles. The reaction during this process was performed under a nitrogen atmosphere. After a predetermined time, cooling was performed to room temperature at a temperature drop rate of 0.5°C / min.

[0283] After cooling, the reaction product was subjected to solid-liquid separation using a 10L pressure filter at a pressure of 0.4 MPa to obtain a toner filter cake. Deionized water was then added to the pressure filter to its full capacity, and washing was performed at a pressure of 0.4 MPa. Washing was performed in this manner for a total of three times. The obtained toner filter cake was dispersed in 1,000 parts of a 50:50 mixed solvent of methanol / water in which 0.15 parts of a nonionic surfactant were dissolved to obtain a surface-treated core particle dispersion.

[0284] The core particle dispersion was poured into a pressure filter, and another 5 L of deionized water was added. Solid-liquid separation was then performed at 0.4 MPa, and the fluidized bed was then dried at 45° C. to obtain core particles 1.

[0285] Production of toner particles 1

[0286] The shell dispersion 1 was added to obtain a resin solid content of 1.0 part relative to 100.0 parts of the solid content of the core particle 1 dispersion. Then, the pH was adjusted to 8.0 by adding a sodium hydroxide aqueous solution at room temperature (about 25° C.) while stirring at a rotation speed of 200 rpm. Then, the temperature was raised to 70° C. and a shell layer was formed on the surface of the core particle by stirring for 2 hours.

[0287] Then, the toner particle dispersion was adjusted to pH 7 (neutral) using hydrochloric acid and the toner particle dispersion was cooled to room temperature. Thereafter, the calcium phosphate dispersant was dissolved by adding hydrochloric acid, and filtered, washed with water, and then dried to obtain toner particles 1 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0288] Production of toner 1

[0289] 100.0 parts of Toner Particles 1 were mixed with 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90", positively charged hydrophobized silica particles, Nippon Aerosil Co., Ltd.) for 3 minutes using an FM mixer (Nippon Coke & Engineering Co., Ltd.) to attach the silica particles to Toner Particles 1. This was then sieved with a 300 mesh sieve (opening = 48 μm) to obtain Toner 1. The properties of the obtained Toner 1 are given in Table 4.

[0290] Production of toners 2 to 19 and 22 to 29

[0291] Toners 2 to 19 and 22 to 29 were obtained by the same production method as used for Toner 1, except for the changes shown in Table 3. The aluminum sulfate aggregating agent was changed to calcium chloride for Toner 14, to magnesium chloride for Toner 15, and to sodium chloride for Toner 22. The properties are given in Table 4.

[0292] Production of Toner 20

[0293] Production of core particles 20

[0294] ·Polyester resin 1 60.0 parts

[0295] · 40.0 parts of styrene-acrylic resin for core particles

[0296] ·CI Pigment Blue 15:3 (Copper Phthalocyanine) 5.0 parts

[0297] · Ester wax (behenyl behenate: melting point = 72°C) 15.0 parts

[0298] Fischer-Tropsch wax 2.0 parts (C105, Sasol Limited, melting point: 105°C)

[0299] 100.0 parts of methyl ethyl ketone

[0300] 100.0 parts of ethyl acetate

[0301] These materials were dispersed using an attritor (Mitsui Mining & Smelting Co., Ltd.) for 3 hours to obtain a colorant dispersion.

[0302] Separately, an aqueous medium was prepared by adding 1.8 parts of magnesium hydroxide to 300.0 parts of deionized water heated to a temperature of 60° C. and stirring at a stirring speed of 10,000 rpm using a TK homomixer (Tokushu Kika Kogyo Co., Ltd.). The colorant dispersion was put into the aqueous medium, and the colorant particles were granulated by stirring at a temperature of 65° C. in an N2 atmosphere at a stirring speed of 12,000 rpm using a TK homomixer for 15 minutes.

[0303] The TK homomixer was changed to a common propeller stirrer. The stirring speed of the stirrer was maintained at 150 rpm; the internal temperature was raised to a temperature of 95° C.; and the solvent was removed from the dispersion liquid by maintaining for 3 hours to prepare a core particle 20 dispersion liquid.

[0304] Production of Toner Particles 20

[0305] The shell dispersion 1 was added to obtain a resin solid content of 1.0 part relative to 100.0 parts of the solid content of the core particle 20 dispersion. Then, the pH was adjusted to 8.0 by adding a sodium hydroxide aqueous solution at room temperature (about 25° C.) while stirring at a rotation speed of 200 rpm. Then, the temperature was raised to 70° C. and a shell layer was formed on the surface of the core particle by stirring for 2 hours.

[0306] Then, the toner particle dispersion was adjusted to pH 7 (neutral) using hydrochloric acid and the toner particle dispersion was cooled to room temperature. Thereafter, the calcium phosphate dispersant was dissolved by adding hydrochloric acid, and filtered, washed with water, and then dried to obtain toner particles 20 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0307] Production of Toner 20

[0308] 100.0 parts of Toner Particles 20 were mixed with 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90", positively charged hydrophobicized silica particles, Nippon Aerosil Co., Ltd.) for 3 minutes using an FM mixer (Nippon Coke & Engineering Co., Ltd.) to allow the silica particles to adhere to the Toner Particles 20. This was then sieved with a 300 mesh sieve (opening = 48 μm) to obtain Toner 20. The above evaluations were performed using Toner 20, and the resulting properties are shown in Table 4.

[0309] Production of Toner 21

[0310] Production of core particles 21

[0311] Polyester resin 1: 60.0 parts

[0312] · 40.0 parts of styrene-acrylic resin for core particles

[0313] CI Pigment Blue 15:3 (Copper Phthalocyanine): 5.0 parts

[0314] · Ester wax (behenyl behenate: melting point = 72°C) 15.0 parts

[0315] Fischer-Tropsch wax: 2.0 parts (C105, Sasol Limited, melting point: 105°C)

[0316] These materials were preliminarily mixed using a Mitsui Henschel mixer (Mitsui Miike Chemical Engineering Machinery Co., Ltd.) and subsequently melt-kneaded using a twin-screw extruder (trade name: PCM-30, Ikegai Ironworks Corporation) with the temperature set to provide a melt temperature of 140° C. at the outlet.

[0317] The obtained kneaded material was cooled and coarsely pulverized using a hammer mill, and then pulverized using a pulverizer (trade name: Turbo Mill T250, Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified using a multi-classifier based on the Coanda effect to obtain core particles 21 having a weight average particle size (D4) of 6.8 μm.

[0318] Production of Toner Particles 21

[0319] An aqueous medium was prepared by adding 1.8 parts of tricalcium phosphate to 250.0 parts of deionized water heated to a temperature of 40° C. and stirring at a stirring speed of 15,000 rpm using a TK Homomixer (Tokushu Kika Kogyo Co., Ltd.).

[0320] The shell dispersion 1 was added to obtain a resin solid content of 1.0 part relative to 100.0 parts of the solid content of the core particle 21 dispersion. Then, the pH was adjusted to 8.0 by adding a sodium hydroxide aqueous solution at room temperature (about 25° C.) while stirring at a rotation speed of 200 rpm. Then, the temperature was raised to 70° C. and a shell layer was formed on the surface of the core particle by stirring for 2 hours.

[0321] Then, the toner particle dispersion was adjusted to pH 7 (neutral) using hydrochloric acid and the toner particle dispersion was cooled to room temperature. Thereafter, the calcium phosphate dispersant was dissolved by adding hydrochloric acid, and filtered, washed with water, and then dried to obtain toner particles 21 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0322] Production of Toner 21

[0323] 100.0 parts of Toner Particles 21 were mixed with 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90", positively charged hydrophobicized silica particles, Nippon Aerosil Co., Ltd.) for 3 minutes using an FM mixer (Nippon Coke & Engineering Co., Ltd.) to allow the silica particles to adhere to Toner Particles 21. This was then sieved with a 300 mesh sieve (opening = 48 μm) to obtain Toner 21. The above evaluation was performed using Toner 21, and the properties obtained are given in Table 4.

[0324] [Table 3]

[0325]

[0326] [Table 4]

[0327]

[0328] In the table, the metal content refers to the polyvalent metal content P(M) (atomic %). The storage elastic modulus at 30 μN is the "surface storage elastic modulus of the toner at 25°C under a load of 30 μN". The storage elastic modulus at 50 μN is the "surface storage elastic modulus of the toner at 25°C under a load of 50 μN". The shell thickness is the average value of the shell thickness (nm).

[0329] Image evaluation

[0330] A color laser beam printer from Hewlett-Packard (HP LaserJet Enterprise Color M652n) was used as the image forming apparatus; it was modified so that the process speed was 400 mm / sec. A Genuine HP 656XLaserJet toner cartridge (cyan) was used for the cartridge.

[0331] The product toner was taken out from the cartridge, followed by cleaning with a blower, and filled with 300 g of the toner to be evaluated. The following evaluation was performed using the above-mentioned image forming apparatus and the cartridge.

[0332] Fogging

[0333] The fogging was evaluated in a high temperature and high humidity environment (30°C / 80% RH). XEROX 4200 paper (75 g / m 2 , Xerox Corporation) was used to evaluate paper.

[0334] Operating under a high temperature, high humidity environment, 20,000 sheets were printed in an intermittent durability printing test in which two sheets of a character E image with a printing rate of 1% were output every four seconds.

[0335] Thereafter, a solid white image was output, and Dr-Ds was used for the fogging value, where Ds was the worst value of the reflection density in the white background area, and Dr was the average reflection density of the transfer material before image formation.

[0336] The reflection density of the white background area was measured using a reflection densitometer (Reflectometer Model TC-6DS, Tokyo Denshoku Co., Ltd.) and using an amber filter as a filter.

[0337] The smaller the value, the better the image fogging level. The evaluation criteria are as follows.

[0338] Evaluation Criteria

[0339] A: less than 0.5%

[0340] B: 0.5% or more and less than 1.5%

[0341] C: 1.5% or more and less than 3.0%

[0342] D: 3.0% or more

[0343] Development streaks (developability)

[0344] The development streak is a vertical streak of about 0.5 mm generated due to the breakage and crushing of the toner, and is an image defect that is easily visible when a full-surface halftone image is output.

[0345] The development streak evaluation was performed in a low-temperature and low-humidity environment (15° C. / 10% RH).

[0346] XEROX 4200 paper (75g / m 2 , Xerox Corporation) was used to evaluate the paper.

[0347] Operating under low temperature and low humidity environment, 20,000 sheets were printed in an intermittent durability printing test in which two sheets of character E images with a printing rate of 1% were output every four seconds. Then, a full-surface halftone image was output and the presence / absence of vertical streaks was checked. The results are given in Table 5.

[0348] Evaluation Criteria

[0349] A: No

[0350] B: Development streaks occur at one to three locations

[0351] C: Development streaks occur in four to six locations

[0352] D: Development streaks occur at seven or more locations, or development streaks with a width of 0.5 mm or more occur

[0353] Fixability

[0354] Solid images were printed on transfer materials at different fixing temperatures (toner loading: 0.9 mg / cm 2 ) and were evaluated using the criteria given below. The fixing temperature is a value measured on the fixing roller surface using a non-contact thermometer. Letter-sized plain paper (XEROX 4200, 75 g / m 2 , Xerox Corporation) was used for transfer materials.

[0355] Evaluation Criteria

[0356] A: No fouling at 140°C

[0357] B: fouling occurs at 140°C

[0358] C: fouling occurs at 150°C

[0359] D: fouling occurs at 160°C

[0360] Blockage (storage)

[0361] 5 g of each specific toner was put into a 50 mL plastic cup; it was left for 3 days at temperature = 55° C. / humidity = 10% RH; then, the presence / absence of aggregated masses was checked and evaluated using the following criteria.

[0362] Evaluation Criteria

[0363] A: No clustering blocks are generated

[0364] B: Slightly aggregated and broken by light pressure of fingers

[0365] C: Agglomerated lumps are produced and are not broken even by lightly pressing with fingers

[0366] D: Completely gathered

[0367] Examples 1 to 21

[0368] The above evaluation was performed using each of Toners 1 to 21 as a toner in Examples 1 to 21. The evaluation results are given in Table 5.

[0369] Comparative Examples 1 to 8

[0370] The above evaluation was performed using each of Toners 22 to 29 as a toner in Comparative Examples 1 to 8. The evaluation results are given in Table 5.

[0371] [Table 5]

[0372]

[0373] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising toner particles, characterized in that: The toner particles include: a core particle comprising a resin component, a shell covering the surface of the core particle, and Polyvalent metals, among which The resin component comprises a polyester resin; The polyester resin comprises a carboxyl group; The shell comprises an amino resin; The multivalent metal is a metal with a valence of two or more; The multivalent metal is present at and near the core particle / shell interface, and the range of 0.85d to 1.15d from the outline of the cross section of the toner particle toward the center of the cross section in a direction perpendicular to the outline represents the core particle / shell interface and the vicinity of the interface, wherein d is the thickness of the shell in nm; In an electron image of a cross section of the toner particle taken using a transmission electron microscope, The content P(M) of the polyvalent metal is 0.0010 to 2.0000 atomic %, the content P(M) being obtained by energy dispersive X-ray analysis during line scanning in a range of 0.85d to 1.15d from the outline of the cross section of the toner particle toward the center of the cross section in a direction perpendicular to the outline, the content P(M) being an atomic weight fraction using all elements detected during the analysis as 100%; and According to nanoindentation measurement of the toner, the toner has a surface storage elastic modulus of 6.50 to 12.00 GPa under a load of 30 μN at 25° C. 2 . The toner according to claim 1 , wherein a surface storage elastic modulus of the toner under a load of 50 μN at 25° C. is from 0.20 to 12.00 GPa according to nanoindentation measurement of the toner. 3 . The toner according to claim 1 , wherein the amino resin is a thermosetting resin. 4 . The toner according to claim 1 , wherein the amino resin is at least one selected from the group consisting of melamine resins, urea-formaldehyde resins, guanamine resins, and aniline resins. 5 . The toner according to claim 1 , wherein the polyvalent metal is at least one selected from the group consisting of Al, Mg, and Ca. 6 . The toner according to claim 1 , wherein an average value of the thickness of the shell is 1.0 to 30.0 nm. 7 . The toner according to claim 1 , wherein the polyvalent metal is Mg derived from magnesium hydroxide. 8 . The toner according to claim 1 , wherein the polyvalent metal is Al derived from aluminum sulfate. 9 . The toner according to claim 1 , wherein the polyvalent metal is Mg derived from magnesium chloride. 10 . The toner according to claim 1 or 2 , wherein the toner further comprises an external additive. 11 . The toner according to claim 1 , wherein the amino resin is a melamine resin.

Citation Information

Patent Citations

  • Toner for electrostatic charge image development

    JP2014164274A

  • Toner for electrostatic latent image development

    JP2015045844A

  • Method of manufacturing toner, toner, two-component developer, developing device and image forming apparatus

    CN101339372A

  • Electrostatic charge image developing carrier, electrostatic charge image developer, developer cartridge, process cartridge, and image forming apparatus

    CN105278271A